Aprendizagem significativa de Botânica em laboratórios vivos - Araújo, Joeliza Nunes (2014)
The teaching of Botany is one of the essential branches of Biology that allows the students’ scientific education and important part of the process of understanding the Amazonian biodiversity. However, the experience of teaching this subject have been showing up in unmotivated and uninteresting way, making the teaching mechanical and with low achievement by student. In this investigation we propose a discussion about possible theoretical and methodological alternatives for teaching of Botany that can promote meaningful learning of content by students. The objective was to investigate the main educational and pedagogical perspectives of science education in a living lab as a not formal space that influencing the development of meaningful learning of concepts in Botany. To achieve this objective we identify methodological aspects that facilitate interaction between prior knowledge and new knowledge about plants and we seek to understand on which methodological conditions a living laboratory may constitute potentially meaningful material for learning concepts of Botany. The methodology used was a qualitative study with a participant observation. The research subjects were 63 (sixty three) students from two classes of 3rd year of high school at a public school in the city of Parintins/AM. The instruments for data collection included desk research, literature review, interviews of students and didacticism sequence. The theoretical references that laid the survey were based on the fundamentals of science education and in the theory of meaningful learning. We also have a teaching sequence that was developed in 5 phases: 1. Lecture-ride the trail. 2. Production of dried specimens; 3. Production of text; 4. Production of the album about the morphology of leaves; 5. Production of conceptual maps. In the results of the interviews we identify students' prior knowledge about plant systematics, plant physiology, genetics and evolution. Among the interviewed students 83% and 17% answered, respectively, who had not attended classes in Botany outdoor classroom and participated in lessons outside the classroom. For 89% of the research subjects, to have class in different spaces of the classroom is better, but 11% said that space makes no difference for the class. In the design of the students is better to study in spaces outside the classroom because it promotes social interaction and awaken them to new interests, apart from that contact with the object of knowledge motivates learning. For those who like Botany, the class location makes no difference to their learning because for them depends on the students themselves and not just the environment. The testimonials are emphatic and show that one of the conditions for meaningful learning is a willingness to learn. Students interested themselves for different contents of the proposal (leaf morphology), for example, they cited the social dimension of botany, genetics, and evolution of plants, plant diversity, environment and ecology, plant physiology, plant anatomy and morphology, plant reproduction, systematic and taxonomy. The interview results corroborate our way of thinking that there is need to study plants in touch with the vegetables themselves, preferably in natural environments, which provides motivation for meaningful learning. The lecture ride was a good example that show that the students themselves can lead the class, and the mediating role of the teacher will be to take advantage of the comments and questions of the students to discuss more detailed aspects of the topic. A contextualized and less fragmented teaching practice, environments and diverse classes were conducive to discussions of the issues. The living laboratory, with appropriate mediation constituted in potentially meaningful material for learning concepts of Botany. As students came in contact with the scientific knowledge in the field of Botany had values formation related to specific and social functions of plants and consequently happened the students' science education. The dried specimens constituted themselves in a technical study material that are in the same time even scientific, different 12 from educational materials that in general they use in basic education. Direct observation of plants contributes greatly to learning than the simple illustration in textbooks. The knowledge acquired during the production of dried specimens about the structures present and/or absent in leaf like limbo, petiole, sheath, veins, stipules was significant for they could identify them and classify the regions as leaves, veining, form, subdivision and board of limbo. If the student has learned significantly the concept of limbo, petiole, sheath, rib, stipule he knows to express his understanding when faced with new learning situation or other school works or even in everyday tasks. The texts produced by the students demonstrate their critical analysis as to the place of study, the model of the biology classes that happen and do not meet. In the production of the album the students learned to classify the morphology of leaves, comparing their observations, their prior knowledge and new knowledge. Concept maps show that the majority (73%) of the students have learned new concepts, some of them showing greater relations between morphological concepts, others adding physiological concepts, showing the integration of meanings. The establishment of the ideas, concepts and propositions will show the clarity of learning as well as help us to realize the shortcomings or difficulties in student learning. In the maps constructed the progressive differentiation and integrative reconciliation are present. We therefore conclude that the construction of this thesis allowed us to think that the value that the student initially know, whether he is predisposed to learn and also know how to choose and use tools and strategies consistent teaching and potentially significant are indispensable for meaningful learning of certain content. We conclude also that not just have a rich living laboratory with materials to teach Botany if students do not feel attracted or if the teacher does not know how to mediate his class to turn it in moments of enchantment.